Design and performance of an HTS wideband microstrip bandpass filter at X‐band. Issue 5 (23rd March 2013) - Shang, Zhaojiang; Guo, Xubo; Cao, Bisong; Zhang, Xiaoping; Wei, Bin; Heng, Yong; Song, Xiaoke; Suo, Guannan; Wang, Jingchen; Li, Qirong
Abstract This article presents a 10‐pole high‐temperature superconducting (HTS) wideband microstrip bandpass filter with a novel configuration and compact size.The filter at 10 GHz with a fractional bandwidth of 40% is designed and fabricated on a 32.6 mm × 6.7 mm × 0.5 mm MgO substrate with double‐sided YBCO films. The internal couplings between quarter‐wavelength resonators are realized by parallel‐coupled microstrip line (PCML) structure and capacitive open‐ended stubs. The strong external couplings required by wideband filter are realized by impedance steps and capacitive stubs. The measured results at 55 K, without any tuning, show a high performance. The insertion loss is less than 0.31 dB, the return loss is better than −14 dB, and the out‐of‐band rejection is higher than 70 dB. The overall measurements are in good agreement with the simulations. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1027–1029, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27485